INCREASING THE INDUSTRIAL POTENTIAL OF A REGION AS A FACTOR OF IMPROVING THE REGION’S COMPETITIVENESS - L. V. Shamray (Russian Journal of Economics and Law)
Objective: to determine the factors of increasing the region competitiveness by defining the industrial potential of its enterprises. Methods: in the research, the systemic, structural, functional, situational, economic analysis was widely used, as well as modelling of the economic entities functioning. The main modeling method used in this work is the model of break-even point widely known and tested in many enterprises. The dependence, proposed by the author, is of analytical character. Results: the article considers different approaches to the definition of competitiveness; the effect of the factors is described. The industrial potential of the enterprises is presented as one of the factors of regional competitiveness. The difference is described between the competitive advantage in commercial and production activities. The author suggests a methodology allowing to evaluate the competitiveness of industrial enterprises through the performance of production capacity, the possibility of making managerial decisions based on the results of its application; the results of the model testing are present. The possibility of applying the model at the regional level is shown. Scientific novelty: the article presents the author’s method allowing to calculate the potential growth of the enterprises competitiveness using the output capacities as the difference between the maximum and actual values of capacity. Practical significance: the use of models in the practice of the company allows to evaluate the enterprise competitiveness, identifying the marginal productivity of the equipment. Once it has been reached, the questions arise: how long the company will remain competitive in achieving 100% capacity utilization; selection of areas of extensive growth due to the fact that the limits of intensive growth have been achieved. Testing of the model was carried out at the Volgograd baking enterprises; it showed a high accuracy of the calculation (the deviation of calculated values from the actual did not exceed 5 %). The author's model is applicable to assess the competitiveness of the region basing on the industrial potential of its enterprises.